77.9k views
2 votes
Solve : - 43 - 4x = 3(1 - 9x)

2 Answers

4 votes

Answer:

The answer is

x = 2

- 43 - 4x = 3(1 - 9x)

Expand the terms

That's

- 43 - 4x = 3 - 27x

Group like terms

Send the constants to the right side of the equation and those with variables to the left side

That's

- 4x + 27x = 43 + 3

Simplify

23x = 46

Divide both sides by 23


(23x)/(23) = (46)/(23)

We have the final answer as

x = 2

Hope this helps you

User Brian Teeter
by
4.5k points
6 votes

Answer:

x = 2

Explanation:

-43 - 4x = 3(1 - 9x)

Distribute the 3:

-43 - 4x = 3 * 1 - 3 * 9x

-43 - 4x = 3 - 27x

Add 27x to both sides:

-43 - 4x + 27x = 3 - 27x + 27x

-43 + 23x = 3

Add 43 to both sides:

-43 + 43 + 23x = 3 + 43

23x = 46

Divide both sides by 23:

23x / 23 = 46 / 23

x = 2

User Matthias Benkard
by
4.3k points